RANCANG BANGUN APLIKASI PENGGAJIAN PADA PT. PERKEBUNAN NUSANTARA VII (PERSERO) SUNGAI NIRU BERBASIS WEB - Aprinsyah Dika Putra Putra; Rishi Suparianto; Andi Christian (Technologia : Jurnal Ilmiah, 2023)
PT. Perkebunan Nusantara VII (Persero) Sungai Niru Unit is a company engaged in agriculture, especially oil palm, rubber, sugarcane and tea which has parts of employee duties, the first is processing, engineering, crafts, operators, laboratories, human resources, general and warehouses. The payroll method at this company has used bank transfers, it's just that, employees have to take payslips to the company. In addition, how to make payslips still uses Mircosoft Office Excel 2010 which has to go through a long process and takes a relatively long time, and also data storage is less secure. The purpose of this study is to build an application using a website to facilitate PT. Perkebunan Nusantara VII (Persero) Sungai Niru Unit in processing employee payroll because it is well computerized and easy to use. The research method uses qualitative descriptive methods with data collection techniques in the form of observation, interviews and literature studies. This type of data consists of qualitative data as well as data sources consist of perimer and secondary data. The device development method uses the waterfall method. System design tools used are use case diagrams, class diagrams and activity diagrams. This application is built using a website with php programming language and Mysql database, as well as to print reports using pdf components.